1992
DOI: 10.1007/bf01832353
|View full text |Cite
|
Sign up to set email alerts
|

Interval cancer and survival in a randomized breast cancer screening trial in Stockholm

Abstract: The aim of the present study was to analyse the survival rate in a group of breast cancers detected in the intervals between screening examinations in relation to clinically detected cancers in a non-screened population. All interval and control cancers were recruited from a randomized controlled mammography screening trial in Stockholm. The overall survival up to eight years of observation was higher in 191 patients with interval cancers than in 142 control cancers (p = 0.01). There were no significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 17 publications
6
22
0
Order By: Relevance
“…24 Frisell et al found no diVerence in survival between true interval cancers and false negative cases. 25 Our findings are compatible with this but it would be ill judged to deduce from them that tumours presenting in the interval after a missed mammographic diagnosis are not diVerent from true interval cancers. Although any diVerences between the two categories lack statistical significance, analysis suggests that our false negative cancers are closer to our symptomatic tumours than true interval cancers in terms of size and grade-divergences that one might anticipate.…”
Section: Discussionsupporting
confidence: 84%
“…24 Frisell et al found no diVerence in survival between true interval cancers and false negative cases. 25 Our findings are compatible with this but it would be ill judged to deduce from them that tumours presenting in the interval after a missed mammographic diagnosis are not diVerent from true interval cancers. Although any diVerences between the two categories lack statistical significance, analysis suggests that our false negative cancers are closer to our symptomatic tumours than true interval cancers in terms of size and grade-divergences that one might anticipate.…”
Section: Discussionsupporting
confidence: 84%
“…We can, however, draw broad comparisons with other European screening programmes and trials with similar overall interval cancer rates, bearing in mind that these have a two year screening interval. The proportion of true interval cancers occurring in the first two years after screening in our series was 60%, similar to that reported in the Nijmegen programme (58%) and Stockholm trial (64%) in women aged 50–64 4 5. Recent changes designed to improve the sensitivity of the screening test are welcome, but we believe that shortening the screening interval is the only way to reduce the number of true interval cancers which will otherwise continue to present in the third year after screening.…”
Section: Commentsupporting
confidence: 89%
“…The conclusions of other authors, however, have not always agreed about these possible differences (Ikeda et al, 1992), as Porter et al, 2006 point out in their recent article. Some authors have suggested the hypothesis that tumours diagnosed in the first year after a screening mammogram (earlypresenting IC) could be more aggressive, having greater lymph-node involvement and a worse histological grade than those diagnosed later (Frisell et al, 1992;Fracheboud et al, 1999). Nevertheless, as in our study, other authors conclude that there are no significant differences between these two groups of tumours in the abovementioned variables or in survival, and that the classical prognostic factors continue to be the ones that are independently associated with survival (Ikeda et al, 1992).…”
Section: Discussionmentioning
confidence: 99%